The legal needs of people receiving palliative care in Uganda: A multi-method assessment to advance universal health coverage - Sofia Weiss Goitiandia; Eve Namisango; Emmanuel B. K. Luyirika; Faith N. Mwangi-Powell; Lynn Atuyambe; Elizeus Rutebemberwa; Paul Muhimbura; Henry Ddungu; Richard A. Powell; Fatia Kiyange; William E. Rosa (Palliative Care and Social Practice)
Background: Palliative care (PC), a holistic approach to care for persons living with serious illness or injury, is a crucial component of Universal Health Coverage (UHC) and Sustainable Development Goal 3. While Uganda has made commendable progress in improving PC access, the legal aspects of PC provision remain underexplored. Objectives: Considering knowledge gaps regarding the legal aspects of PC in Uganda, this study sought to assess the legal needs and challenges faced by persons receiving PC in the country. Design: Cross-sectional design utilizing both quantitative and qualitative methods. Methods: The quantitative arm surveyed 384 individuals receiving PC across three study sites, comprising public and not-for-profit private healthcare institutions. Quantitative data were analyzed descriptively. The qualitative arm involved 25 key informant interviews conducted with healthcare providers, legal and human rights experts, and medicines supply chain professionals, along with four focus group discussions involving 40 individuals receiving PC at two study sites. Qualitative analysis was used to analyze the qualitative data. Results: Both quantitative and qualitative findings revealed significant legal challenges and practical obstacles faced by persons receiving PC in Uganda. Participants reported a lack of access to high-quality PC services, including legal assistance. Legal challenges included limited awareness of patients’ legal rights, the need for increased legal support in areas such as succession planning and will-making, and legal barriers associated with ensuring an adequate supply of opioids for pain management. Conclusion: Based on findings of unmet legal needs among individuals receiving PC in Uganda, this study provides recommendations to address these needs, strategically and pragmatically maximizing patients’ quality of life and well-being and advancing PC provision as part of UHC. Trial registration: Not applicable.